Sandwich-structured nano/micro fiber-based separators for lithium metal batteries. (January 2019) - Pan, Ruijun; Sun, Rui; Wang, Zhaohui; Lindh, Jonas; Edström, Kristina; Strømme, Maria; Nyholm, Leif
Abstract: Although the increased need for high-energy/power-density energy storage systems has revived the research on lithium metal batteries (LMBs), the influence of the separator on the performance of LMBs is still generally neglected. In the present study, a sandwich-structured separator (referred to as the CGC separator below) composed of two 2.5 µm thick cellulose nanofiber (CNF) surface layers and an intermediate 15 µm thick glass microfiber (GMF) and CNF composite layer is described. While the CNF surface layers of the CGC separator feature a homogeneous distribution of nano-sized pores favoring the attainment of a homogeneous current distribution at both electrodes, the intermediate GMF/CNF layer contains macropores facilitating the ionic transport through the separator. The CGC separator exhibited a much better electrolyte wettability and thermal stability compared to a Celgard separator, due to the use of the hydrophilic and thermally stable CNFs and GMFs. It is also shown that the combination of nano-sized and micro-sized fibers used in the CGC separator yields a higher ionic conductivity than that for the commercial separator (1.14 vs. 0.49 mS cm −1 ). Moreover, the influence of the separator pore structure (e.g. the porosity and pore distribution) on the performance of LMBs is studied for both Li anodes and LiFePO4 composite cathodes. The results demonstrate that the use of separators with high porosities and homogeneous surface pore distributions can improve the performances (e.g. capacities and stabilities) of LMBs considerably, and also highlights the importance of proper separator/electrode interactions. The present approach constitutes a practical engineering strategy for the production of separators with nano/micro fibers and a promising route for the development of LMBs with improved safety and enhanced electrochemical performances. Graphical abstract: fx1 Highlights: Sandwich-structured separators based on cellulose nano and glass microfibers. Homogeneous separator pore structures yield homogeneous current densities. Increased safety and performance via high thermal stability and wettability. Lithium-metal batteries with improved life times and rate capabilities. Provides increased capacity utilization of the positive electrode.